Corrosion Stability and Biological Activity of Anodized cpTi for Dental Application - Aleksandra S. Popović; Minja Miličić Lazić; Dijana Mitić; Lazar Rakočević; Dragana Jugović; Predrag Živković; Branimir N. Grgur (Metals)
The anodic oxidation of titanium implants is a practical, cost-effective method to enhance implant success, especially due to rising hypersensitivity concerns. This study investigated the electrochemical behavior, surface characteristics, and biocompatibility of anodized commercially pure titanium (cpTi, grade IV). Anodization is performed on polished, cleaned cpTi sheet samples in 1 M H2SO4 using a constant voltage of 15 V for 15 and 45 min. The color of the oxide layer is evaluated using the CIELab color space, while composition is analyzed by a scanning electron microscope (SEM) equipped with an energy dispersive spectrometer (EDS). Additionally, X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) are performed to identify and monitor the phase transformations of the formed titanium oxides. Corrosion measurements are performed in 9 g L−1 NaCl, pH = 7.4, and show the excellent corrosion stability of the anodized samples in comparison with pure titanium. The biological response is assessed by determining mitochondrial activity and gene expression in human fibroblasts. Anodized surfaces, particularly Ti-45, promote higher mitochondrial activity and the upregulation of adhesion-related genes (N-cadherin and Vimentin) in human gingival fibroblasts, indicating improved biocompatibility and the potential for enhanced early soft tissue integration.